Price transparency in residential electricity: Experiments for regulatory policy - Pete Lunn; Marek Bohacek (The Economic and Social Research Institute (ESRI), 2016)
Two laboratory studies investigated the effect of price transparency on consumers' decision-making in the residential electricity market. The first tested whether consumers have difficulties when confronted with unit prices expressed as discounts from standard rates, which vary between suppliers. Results showed that consumers were much more likely to choose packages with low unit prices when unit prices were presented explicitly rather than as discounts. When discounts were described as percentages, consumers' decisions were also less accurate. The second study pre-tested the likely impact of a potential mandatory "estimated annual bill" (EAB) on marketing material, calculated for a customer with average usage. Results demonstrated that consumers were more likely to judge value according to unit prices when an EAB appeared on advertisements. Moreover, when unit prices were communicated via an EAB rather than a discount, consumers chose lower unit price offerings and were more precise in their decision-making. The findings suggest that the EAB is likely to be beneficial for consumers' decision-making.
Keywords: C91; D18; Q41; 330; energy; price transparency; estimated annual bill; mandated simplification; consumer protection